2005
DOI: 10.1038/sj.jhh.1001897
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype association analysis of the polymorphisms Arg16Gly and Gln27Glu of the adrenergic β2 receptor in a Swedish hypertensive population

Abstract: The Arg16Gly and the Gln27Glu polymorphisms in the gene for the b 2 -adrenergic receptor (b 2 AR) have been linked to an increased risk for cardiovascular disease. The aim of the present study was to evaluate the significance of these haplotypes for development of myocardial infarction (MI) as well as other cardiovascular phenotypes. In a prospective study cohort (CAPPP), 522 hypertensive patients (174 MI and 348 matched controls) were analysed for the Arg16Gly and the Gln27Glu polymorphisms by dynamic allele-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
1
17
0
4
Order By: Relevance
“…Hermann et al (15) showed that four of the ADRB2 gene polymorphisms, named C19R, T220C, Arg16Gly, Gln27Glu, were not associated with MI and hypertension. Wallerstedt et al (19) found that neither haplotypes nor genotypes of the Arg16Gly and Gln27Glu polymorphisms in the ADRB2 gene were associated with MI in Caucasian hypertensive subjects. In another study, although the genotype distribution of the ADRB2 Gly16Arg and Gln27Glu polymorphisms was not significantly different between MI patients and control subjects, the ADRB2 Thr164Ile polymorphism was found to be significant between MI patients and control subjects (20).…”
Section: Resultsmentioning
confidence: 98%
“…Hermann et al (15) showed that four of the ADRB2 gene polymorphisms, named C19R, T220C, Arg16Gly, Gln27Glu, were not associated with MI and hypertension. Wallerstedt et al (19) found that neither haplotypes nor genotypes of the Arg16Gly and Gln27Glu polymorphisms in the ADRB2 gene were associated with MI in Caucasian hypertensive subjects. In another study, although the genotype distribution of the ADRB2 Gly16Arg and Gln27Glu polymorphisms was not significantly different between MI patients and control subjects, the ADRB2 Thr164Ile polymorphism was found to be significant between MI patients and control subjects (20).…”
Section: Resultsmentioning
confidence: 98%
“…Thus, overall data suggest that the ADRB2 polymorphisms may influence vascular responses to a beta2-agonist. In addition, the Gln27 receptor has been associated with increases in systolic blood pressure [49]. …”
Section: Adrb2: Gln27glu; 318c >G (Rs1042714)mentioning
confidence: 99%
“…2830 Bray et al reported significantly higher blood pressures in participants with ADRB2 genotypes Gly16/Gly16 or Gly16/Arg16, proxied in our analysis by rs17778257, and higher frequencies of the Glu27 genotype among hypertensive individuals.. 28 However, opposite results have also been suggested; in another study of 522 hypertensive adults, the ADRB2 Gln27/Gln27 genotype was associated with higher systolic BP compared to Gln27/Glu27 genotype. 31 It is also important to note, however, that several other studies did not find an association with the Arg16Gly and Gln27Glu polymorphisms and hypertension phenotypes. 32,33 One potential explanation for these disparate findings is the lack of haplotype analyses, an especially relevant consideration as the Arg16Gly and Gln27Glu polymorphisms are tightly linked.…”
Section: Discussionmentioning
confidence: 91%